Hybrid vigour among newly evolved bivoltine hybrids of silkworm (Bombyx mori) under Hill conditions - RAJALAKSHMI, E; CHAUHAN, T P S; KAMBLE, C K (The Indian Journal of Agricultural Sciences, 2013)
Heterosis studies on rearing and cocoon characters of 23 new bivoltine hybrids revealed that manifestation of heteroisis was highly significant for all the silk yield contributing characters especially cocoon yield by weight among all the hybrids. Ten new bivoltine hybrids were highly promising over the existing check hybrid (’Ka’x’NB 4D2’). Four hybrids namely ’CNR 14’x’NB4 D2’,’CNR12’x’NB 4D2’and’CNR 13’x’NB 4D2’ exhibited significantly positive heterobeltosis and standard heterosis for most of the characters.